The role of microRNA-107 in Toll-like receptor signaling - Hennessy, Elizabeth J. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2010)
MicroRNAs (miRNAs) are a novel class of small non-coding RNA regulatory molecules which post-transcriptionally regulate genes in a fine-tuning manner. Multiple miRNAs have been shown to be regulated by Toll-like receptors (TLRs), including miR-146a, miR-155 and miR-21. In this study, I have found that the TLR4 ligand lipopolysaccharide (LPS) can down-regulate microRNA-107 (miR- 107). miR-107 is downregulated in response to LPS in many cell lines as well as in primary mouse and human cells.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin.